2021
DOI: 10.21608/bfsa.2021.207160
|View full text |Cite
|
Sign up to set email alerts
|

IN-VITRO INHIBITION OF TYPE 2 DIABETES KEY ENZYMES; EFFECT OF EXTRACTS AND SOLVENT-SOLVENT FRACTIONS OF DANIELLIA OLIVERI (ROLFE) HUTCH. & DALZIEL

Abstract: Daniellia oliveri is a tree species belonging to the subfamily Caesalpinioideae (Leguminosae), whose young leaves are used locally to manage type 2 diabetes in Nigeria. This study aims at evaluating the inhibitory potentials of its crude ethanolic extract (Do-C) and solvent-solvent fractions (n-hexane (Do-H), diethyl ether (Do-D), and ethyl acetate (Do-E)) obtained from Do-C on α-amylase, α-glucosidase activities in-vitro and 1,1-diphenyl-2picraylhydrazine (DPPH) radical scavenging activity using standard prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Inclusively, the antidiabetic property of the various parts (leaves, stem bark and roots) of the plant in various extracts (aqueous, hydroethanol, ethanol) have been investigated in both in vitro and in vivo models [ 26 – 30 ]. Ethanol extract and fractions (hexane, diethyl ether and ethyl acetate) in a study by Adeyemi et al [ 29 ] showed comparative inhibition with acarbose against alpha-amylase with a superior effect over the standard against alpha-glucosidase. Additionally, aqueous root extract at 250 mg/kg body weight (b.w.)…”
Section: Introductionmentioning
confidence: 99%
“…Inclusively, the antidiabetic property of the various parts (leaves, stem bark and roots) of the plant in various extracts (aqueous, hydroethanol, ethanol) have been investigated in both in vitro and in vivo models [ 26 – 30 ]. Ethanol extract and fractions (hexane, diethyl ether and ethyl acetate) in a study by Adeyemi et al [ 29 ] showed comparative inhibition with acarbose against alpha-amylase with a superior effect over the standard against alpha-glucosidase. Additionally, aqueous root extract at 250 mg/kg body weight (b.w.)…”
Section: Introductionmentioning
confidence: 99%